2014
DOI: 10.1155/2014/359630
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal Activity of Jasminum sambac against Malassezia sp. and Non-Malassezia sp. Isolated from Human Skin Samples

Abstract: Malasseziasp. causes skin diseases such as pityriasis versicolor, folliculitis, and atopic dermatitis. The present study aims to evaluate the antifungal activity ofJ. sambacor Arabian jasmine, a flowering plant abundant in the Southeast Asia againstMalasseziasp. using disc diffusion and broth microdilution method. The methanol extract and essential oil from the flowers and leaves ofJ. sambacwere, respectively, prepared using solvent extraction and hydrodistillation process. Skin samples from individuals with d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…A previous study showed that jasmine caused 100% inhibition of spore germination of oto-mycotic pathogens, including C. albicans [ 55 ]. Further, jasmine EO showed promising inhibitory effects against Malassezia species isolated from skin infections [ 22 ], as well as oral strains of Candida species [ 56 ], and a recent study reported its fungicidal activity against mold fungi [ 57 ]. However, none of these studies evaluate the anti-virulence potential of jasmine oil.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study showed that jasmine caused 100% inhibition of spore germination of oto-mycotic pathogens, including C. albicans [ 55 ]. Further, jasmine EO showed promising inhibitory effects against Malassezia species isolated from skin infections [ 22 ], as well as oral strains of Candida species [ 56 ], and a recent study reported its fungicidal activity against mold fungi [ 57 ]. However, none of these studies evaluate the anti-virulence potential of jasmine oil.…”
Section: Discussionmentioning
confidence: 99%
“…Many EOs have the potential to be used as antifungal agents [ 18 , 19 ]. For example, clove and cinnamon oils exhibited strong activity against fluconazole-resistant C. albicans strains [ 20 ], rosemary oil showed promising antifungal effects against C. albicans and Aspergillus niger [ 21 ], while jasmine oil has antifungal activity against dermatophytes [ 22 ]. The antimicrobial activity of plant oils is mainly attributable to a number of phenolic, alcoholic and terpenoid compounds [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…All the tanks showed negative samples for those collected three hours after EOBF application. parahaemolyticus, which are considered pathogenic to shrimp [15,16] . Vibrio alginolyticus, which grows as a yellow-coloured colony, is considered not pathogenic to shrimp [15,16] .…”
Section: Overall View Of Vibrio Count By Tcbs Agar In the Post-larvae Production Facility Before And Three Hours After Eobf Sprayingmentioning
confidence: 99%
“…The callous extracts of J. sambac were also reported to display antimicrobial activity against Staphylococcus albus , Proteus mirabilis , Salmonella typhi, and Propionibacterium acnes 80,81 . The use of J sambac extract can be a potential additive in skin and hair products to prevent Malassezia sp infection altogether.Santhanam et al (2014) indicated that methanol extract of flowers exhibited twice inhibitory effect against Malassezia sp compared to leaves 82 …”
Section: Herbal Treatmentsmentioning
confidence: 99%